One-pot and eco-friendly synthesis of silver nanocrystals using Adiantum raddianum: Toxicity against mosquito vectors of medical and veterinary importance - Govindarajan, Marimuthu; AlQahtani, Fatma Saeed; AlShebly, Mashael Marzouq; Benelli, Giovanni (Journal of Applied Biomedicine, 2017)
Mosquitoes (Diptera: Culicidae) represent a key threat for millions of humans and animals worldwide, since they act as vectors for devastating parasites and pathogens. Eco-friendly control tools are a priority. Plant-mediated biosynthesis of nanoparticles is rapid and cost-effective. Here we biosynthesized poly-dispersed silver nanocrystals (AgNPs) using a cheap aqueous leaf extract of Adiantum raddianum. AgNPs were characterized by UV–vis spectrophotometry, Fourier transform infrared spectroscopy (FTIR), scanning electron microscopy (SEM), transmission electron microscopy (TEM), energy-dispersive spectroscopy (EDX) and X-ray diffraction analysis (XRD). The acute toxicity of A. raddianum extract and biosynthesized AgNPs was evaluated against larvae of the malaria vector Anopheles stephensi, the dengue vector Aedes aegypti and the filariasis vector Culex quinquefasciatus. Compared to the leaf aqueous extract, AgNPs showed higher toxicity against An. stephensi, Ae. aegypti and Cx. quinquefasciatus with LC50 values of 10.33, 11.23 and 12.19 μg/ml, respectively. Biosynthesized AgNPs were found safer to non-target organisms Diplonychus indicus, Anisops bouvieri and Gambusia affinis, with respective LC50 values ranging from 517.86 to 635.98 μg/ml. Overall, this study firstly shed light on the potential of A. raddianum as a potential bio-resource for rapid, cheap and effective nanosynthesis of novel mosquitocides.
Keywords: Disease Vectors; Filariasis; biologická kontrola škůdců; moskyti - kontrola; filarióza; malárie; Adiantum; Plant Extracts; rostlinné extrakty; Pest Control, Biological; infekce přenášené vektorem; Nanoparticles; nanotechnologie; Nanotechnology; Mosquito Control; nanočástice; Malaria